Knockout of ABC transporters by CRISPR/Cas9 contributes to reliable and accurate transporter substrate identification for drug discovery - Feng, Dongyan; Zhong, Guorui; Zuo, Qingxia; Wan, Yanbin; Xu, Wanqing; He, Changsheng; Lin, Cailing; Huang, Dongchao; Chen, Feng; Huang, Lizhen (Frontiers in Pharmacology, 2022)
It is essential to explore the relationship between drugs and transporters in the process of drug development. Strong background signals in nonhuman MDCK or LLC-PK1 cells and overlapping interference of inhibitors or RNAi in human Caco-2 cells mean that an ideal alternative could be to knock out specific transporter genes in Caco-2 cells. However, the application of gene knockout (KO) to Caco-2 cells is challenging because it is still inefficient to obtain rapidly growing Caco-2 subclones with double-allele KO through long-term monoclonal cultivation. Herein, CRISPR/Cas9, a low cost but more efficient and precise gene editing technology, was utilized to singly or doubly knockout the P-gp, BCRP, and MRP2 genes in Caco-2 cells. By combining this with single cell expansion, rapidly growing transporter-deficient subclones were successfully screened and established. Bidirectional transport assays with probe substrates and three protease inhibitors indicated that more reliable and detailed data could be drawn easily with these KO Caco-2 models. The six robust KO Caco-2 subclones could contribute to efficient in vitro drug transport research.